2016
DOI: 10.1039/c6em00012f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into atmospheric PM2.5-borne PAHs in Eastern cities of China: concentration, source diagnosis and health risk assessment

Abstract: This study investigated PM2.5-PAHs associations collected in Beijing, Jinan, and Shanghai in Eastern China. The results indicated that PM2.5 concentrations in Beijing, Jinan, and Shanghai were 125.7 μg m(-3) (18.6-355.5 μg m(-3)), 115.9 μg m(-3) (44.2-345.4 μg m(-3)), and 85.1 μg m(-3) (24.3-232.8 μg m(-3)), respectively. The PAH concentrations in terms of PM2.5 in Beijing, Jinan, and Shanghai ranged from 23.2 to 819.8 ng m(-3), 25.7 to 727.1 ng m(-3), and 8.5 to 133.9 ng m(-3), respectively. PAH concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
1
21
1
Order By: Relevance
“…The presence of these compounds in atmospheric particulate matter, as characterized by Factor 2, might be explained by the motor vehicle emissions with unburned diesel fuel and gasoline. These findings were supported by Li et al (2016b), who reported that oil and coal combustion and diesel and gasoline emissions were the main sources of polycyclic aromatic hydrocarbons in eastern China.…”
Section: Principal Component Analysissupporting
confidence: 77%
See 1 more Smart Citation
“…The presence of these compounds in atmospheric particulate matter, as characterized by Factor 2, might be explained by the motor vehicle emissions with unburned diesel fuel and gasoline. These findings were supported by Li et al (2016b), who reported that oil and coal combustion and diesel and gasoline emissions were the main sources of polycyclic aromatic hydrocarbons in eastern China.…”
Section: Principal Component Analysissupporting
confidence: 77%
“…Principal component analysis (PCA) was employed to analyze the independent source tracers (Li et al, 2006;Hong et al, 2007;Li et al, 2016b) for 19 PAHs, and the factors are listed in Table 2. Two factors accounted for 93.5% of the total variance of the data.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…The concentrations of 12 kinds of PAHs during the heating period from the coal-burning period to the gas-burning period Through the UNGHP, the average concentrations of PM 2.5 -bound As and Mn in the rural area during the gas-burning period were reduced to 8.29 and 39.57 ng/ m 3 , which were even lower than those of Chengdu (As: 40.5 ng/m 3 ; Mn: 137.6 ng/m 3 ) and Shanghai (Mn: 132 ng/m 3 ) where the coal burning was the main heating source at that time (Li et al, 2016a(Li et al, , 2016bWang et al, 2013). However, the annual average concentrations of As and Mn in Seoul of Korea in 2005 were 1.5 and 10.4 ng/m 3 , which were lower than the results of this study (Park et al, 2008).…”
Section: Tablementioning
confidence: 74%
“…It indicated that only Mn in the urban area during the gas-burning period could lead to the noncarcinogenic effect. The HQ of the PM 2.5 -bound Mn was 3.06 in Chengdu in 2009, so people in Tianjin suffered the less harm from Mn through the UNGHP (Li et al, 2016a(Li et al, , 2016b. In this study, the lifetime cancer risk of Ni fell from 1.65 9 10 -6 in the coalburning period to 0.92 9 10 -6 in the gas-burning period in the rural area, which was lower than the limit of 1.1 9 10 -6 , suggesting no potential carcinogenic risk of Ni in the rural area after implementing the UNGHP (Lin et al, 2016).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation